Implementation of a Cooking Bus intervention to support cooking in schools in Wales, UK. Issue 3 (3rd April 2017) - Segrott, Jeremy; Holliday, Jo; Murphy, Simon; Macdonald, Sarah; Roberts, Joan; Moore, Laurence; Phillips, Ceri
Abstract : Purpose: The teaching of cooking is an important aspect of school-based efforts to promote healthy diets among children, and is frequently done by external agencies. Within a limited evidence base relating to cooking interventions in schools, there are important questions about how interventions are integrated within school settings. The purpose of this paper is to examine how a mobile classroom (Cooking Bus) sought to strengthen connections between schools and cooking, and drawing on the concept of the sociotechnical network, theorise the interactions between the Bus and school contexts. Design/methodology/approach: Methods comprised a postal questionnaire to 76 schools which had received a Bus visit, and case studies of the Bus' work in five schools, including a range of school sizes and urban/rural locations. Case studies comprised observation of Cooking Bus sessions, and interviews with school staff. Findings: The Cooking Bus forged connections with schools through aligning intervention and schools' goals, focussing on pupils' cooking skills, training teachers and contributing to schools' existing cooking-related activities. The Bus expanded its sociotechnical network through post-visit integration of cooking activities within schools, particularly teachers' use of intervention cooking kits. Research limitations/implications: The paper highlights the need for research on the long-term impacts of school cooking interventions, and better understanding of the interaction between interventions and school contexts. Originality/value: This paper adds to the limited evidence base on school-based cooking interventions by theorising how cooking interventions relate to school settings, and how they may achieve integration.